Influence of gingivitis in preterm delivery on serum biomarkers COX-2 and PGE-2 - Shaden Husham Maddah*1 - Ghada Ibrahim Taha2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Periodontal disease increases local and systemic inflammatory responses in pregnant women, which may lead to premature delivery. The aim of this study to detect maternal serum levels of Prostaglandin E2 and Cyclooxigenase-2, and evaluate the association between these biomarkers with preterm delivery in pregnant women suffering from gingivitis. A total of 85 pregnant women having gingivitis were divided into three groups; twenty-five preterm-delivery pregnant and thirty full-term delivery pregnant women, in addition to thirty healthy pregnant women with healthy gingiva as a control group. The mean age of patients was (25.07±1.097), (26.12±1.400) years, and (27.73±1.250) years for control group. The blood sample was collected with all participants and the biomarkers cytokines Prostaglandin E2 and cyclooxygenase-2 were detected by enzyme-linked immunosorbent assay (ELISA) kits. The current study showed an increase higher in levels of Prostaglandin E2 and cyclooxygenase-2 in pre-term delivery having gingivitis group followed by full term-delivery pregnant groups having gingivitis compared with a control group, with statistically highly significant differences (p<0.05). This finding indicated that the pre-term delivery women higher than full-term-delivery pregnant revealed worsened periodontal health conditions and elevated levels of serum Prostaglandin E2 and cyclooxygenase-2 levels compared with control group.